PENGARUH PERTUMBUHAN ASET DAN PERTUMBUHAN PENJUALAN TERHADAP RETURN SAHAM DENGAN RETURN ON ASEETS (ROA) SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN - Manul, Yustina Angela; Halim, Abdul; Sulistyo, Sulistyo (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2017)
Investment is one of the important means in improving the ability to collect and maintainwealth. One of the investment options that can be done is through stock investment in the capitalmarket. Investor's expectation in investing is getting the profit level termed with stock return. Return isthe goal of the investor to invest in the capital market. Investors perform various ways in order to getthe desired return desired, by doing their own analysis on the trading behavior of a stock, or by usingthe means already provided from analysts in the capital market. The information that can be used as abenchmark of stock returns of companies studied is ROA, asset growth, and sales growth. This studyaims to determine the effect of asset growth and sales growth on Stock Return through Return OnAseets (ROA) on manufacturing companies listed in Indonesia Stock Exchange (IDX) period 2015-2016. This study using Simple random sampling is used to get the number of samples. Based on thetechnique, 36 companies were obtained as samples. Path analysis technique used in this research withthe result that the higher level of ROA, asset growth, and sales growth hence the higher stock returnalso.